Intraface: Negotiating Gender-Relations in Agrobiodiversity - Padmanabhan, Martina (My University, 2016)
The diversity of plants and animals in agriculture is a social-ecological artefact per se and the result of long-term interaction between humans and agrobiodiversity, displaying the material resistance of the latter. The conceptual framework intraface aims at the analysis of the gendered organization of varieties in an inter- and transdisciplinary research setting. The “negotiations at the intraface” contribute to synthesizing disciplinary perspectives and life-worldly knowledge with a focus on sustainability outcomes with special emphasis on gendered power and interests. The eminent loss of agrobiodiversity requires transdisciplinary knowledge integration for sustainable transformation. The procedure of intraface analysis is illustrated on the case of paddy-rice diversity in Kerala, South India.
Keywords: Agrobiodiversität; Indien; Intraface; Transdsiziplinarität; Verhandlungen; ddc:300